2010
DOI: 10.1037/a0020833
|View full text |Cite
|
Sign up to set email alerts
|

Parenting self-efficacy and parenting practices over time in Mexican American families.

Abstract: Drawing on social cognitive theory, this study used a longitudinal cross-lagged panel design and a structural equation modeling approach to evaluate parenting self-efficacy's reciprocal and causal associations with parents' positive control practices over time to predict adolescents' conduct problems. Data were obtained from teachers, mothers, and adolescents in 189 Mexican American families living in the southwest U.S. After accounting for contemporaneous reciprocal relationships between parenting self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 41 publications
10
78
2
3
Order By: Relevance
“…Results reveal coherent patterns of relations which support the validity of the measures in our sample. For example, children whose personality was agreeable, conscientious, emotionally stable, and open to experience displayed lower levels of externalizing behavior (Prinzie, van der Sluis, de Haan, & Deković, 2010); parents' self-efficacy beliefs were negatively related to children's externalizing behavior (Dumka et al, 2010) and positively to personality traits in children (Meunier, Roskam, Stievenart, van de Moortele, Browne, & Kumar, 2011); the five personality factors were not totally independent of each other, either for children or adults (as already indicated by previous validation studies [Plaisant et al, 2005;Roskam et al, 2000]). …”
Section: Preliminary Analysesmentioning
confidence: 59%
“…Results reveal coherent patterns of relations which support the validity of the measures in our sample. For example, children whose personality was agreeable, conscientious, emotionally stable, and open to experience displayed lower levels of externalizing behavior (Prinzie, van der Sluis, de Haan, & Deković, 2010); parents' self-efficacy beliefs were negatively related to children's externalizing behavior (Dumka et al, 2010) and positively to personality traits in children (Meunier, Roskam, Stievenart, van de Moortele, Browne, & Kumar, 2011); the five personality factors were not totally independent of each other, either for children or adults (as already indicated by previous validation studies [Plaisant et al, 2005;Roskam et al, 2000]). …”
Section: Preliminary Analysesmentioning
confidence: 59%
“…This reasoning is analogous to research on the role of control in the workplace in the prediction of psychological well-being (job demand control model; Pelfrene et Maes, 1999), the relation of work locus of control to well-being (Spector et al, 2002), and findings showing that the general sense of control is a predictor of increased life satisfaction and well-being, especially for individuals lrom lower income groups (Lachman & Weaver, 1998). In comparison to the Creed et al (2012) model, using selfefficacy and optimism as distinct constructs predicting volition, as opposed to observed indicators, allowed for a more complete understanding of what predicts volition and aligns with past research, which has found optimism and self-efficacy to each be predictors of control in specific domains (Dumka, Gonzales, Wheeler, & Millsap, 2010;Ruthig, Hanson, & Marino, 2009). Additionally, allowing optimism and self-efficacy to both directly and indirectly predict life satisfaction aligns with past research linking each of these variables directly to satisfaction (Nes & Segerstrom, 2006;Singley et al, 2010) and allows for a maximal amount of variance in life satisfaction to be explained.…”
Section: The Present Studymentioning
confidence: 64%
“…We used adolescents' self-reports of three different types of externalizing (Galambos & Maggs, 1991), as indicators of an overall externalizing latent variable. Similar adolescent reported measures have been used in earlier studies (e.g., Dumka et al, 2010), and have been related both to parenting practices and PSE. Adolescents reported how often they had engaged in 28 behaviors that covered three areas: (a) disobedience toward parents (seven items, e.g., "Stay out past curfew" and "Lie to parents"), (b) school misconduct (eight items, e.g., "Cut a class" and "Talk back to teachers"), and (c) antisocial behaviors (13 items, e.g., "Get into a physical fight" and "Damage property on purpose").…”
Section: Methodsmentioning
confidence: 84%